VALIDASI E-BOOK BERWAWASAN KARAKTER PADA PEMBELAJARAN PPKN UNTUK SISWA KELAS VI SEKOLAH DASAR - Christanty Rahayu; Wendri Wiratsiwi (Prodi PGSD Universitas PGRI Ronggolawe, 2022)
At this time, education in Indonesia is based on the 2013 curriculum which prioritizes Strengthening Character Education (PPK). The purpose of this study in general is to develop a character-oriented E-Book in learning Civics for grade VI elementary schools, and specifically aims to describe the validity of the E-Book that has been developed. With the character-oriented E-Book, it is hoped that it can help teachers integrate character values in the learning process. The method used in this research is R&D (Reaserch and Development) using the ADDIE model. There are 5 stages of the ADDIE model, namely analyze, design, develop, implement, and evaluate. The data collection technique in this research is a questionnaire. The data collection instrument used is the validation sheet of material experts and media experts. The results of the validation test with experts obtained the criteria of